PENDUGAAN RAGAM GENETIK DAN HERITABILITAS BEBERAPA GENOTIPE PADI TIPE BARU (PTB) - Dulbari Dulbari; Destieka Ahyuni; Nyimas Sa’diyah; Muhammad Kamal (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2023)
This study aims to determine the genetic variance and heritability of yield component and agronomic character of some new plant type (NTP) of rice genotypes planted on two different locations. The research was arranged in randomized complete block design (RCBD) with 12 treatments and three replications as a blok was nested in location (in two locations, i.e.: East Lampung and Tanggamus. The treatment consisted of 10 new type of rice genotypes, i.e.: IPB 3S, IPB 4S, IPB 5R, IPB6R, IPB117-F-7-2-1, IPB 117-F-7-7- 1, IPB 117-F-14-4-1, IPB 117-F-15-4-1, IPB 117-F-20-1-1, IPB 117-F-80- 2-1, and two control varieties, i.e.: Ciliwung and Ciherang. The flowering time, harvesting time, percent of filled grain per panicle, weight of 1000 grains, dray weight of plant, and yield potential have large genetic variability. Plant height, number of tillers, number of productive tillers, flowering time, harvesting time, panicle length, number of filled grain per panicle, number of grain sterility per penicle, percent of filled grain per penicle, weight of 1000 grains, weight of grain per panicle, and dry weight of plant have high heritability. Selection of NPT of rice genotypes was effective because its have wide genetic variability and can be done at an early stage in a character with high heritability.